1998
DOI: 10.1076/ocii.6.4.239.4026
|View full text |Cite
|
Sign up to set email alerts
|

Retinal immunopathology in horses with uveitis

Abstract: These results suggest that retinal pathology may be a primary immunological event in equine uveitis, provide evidence that leptospira-associated uveitis may be a distinct subset of equine uveitides, underscore the relevance of the study of equine uveitis to human uveitis, and support the plausibility of a post-infectious immunopathogenesis of some naturally occurring uveitides in both humans and horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 8 publications
1
31
0
Order By: Relevance
“…Retinal damage in horses with uveitis is related to the presence of B lymphocytes in the retina (318). Antiplatelet antibodies have been demonstrated in human leptospirosis (144,339).…”
Section: Immune Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal damage in horses with uveitis is related to the presence of B lymphocytes in the retina (318). Antiplatelet antibodies have been demonstrated in human leptospirosis (144,339).…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…Equine recurrent uveitis appears to be an autoimmune disease (358,443), and Faine (211) suggested that late-onset uveitis in humans may result from an autoimmune reaction to subsequent exposure. Immune involvement in retinal pathology has been demonstrated in horses with spontaneous uveitis (318). Leptospires have been isolated from the human eye (16), and more VOL.…”
Section: Chronic or Latent Infectionmentioning
confidence: 99%
“…The worldwide distribution of this potentially fatal zoonotic infection and its association with autoimmune disease (12,23,35) provide the impetus to develop an effective and safe vaccine. Prevention of leptospirosis in dogs is accomplished to some extent by inoculation with bacterins that contain the most commonly encountered serovars.…”
mentioning
confidence: 99%
“…Symptoms of infection vary from subclinical to potentially fatal with multiorgan involvement (30,38,50). Immune-based uveitis leading to blindness (12,26,40,51) is a devastating sequela in humans and horses. Survival of the organism in water and persistent urinary shedding by wildlife, rodents, and livestock complicate control of the disease (30,50).…”
mentioning
confidence: 99%